2023
DOI: 10.3390/cells12131708
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the Complement Cascade: Insights into Systemic Immunosenescence and Inflammaging in Age-Related Macular Degeneration and Current Barriers to Treatment

Abstract: Landmark genetic studies have revealed the effect of complement biology and its regulation of the pathogenesis of age-related macular degeneration (AMD). Limited phase 3 clinical trial data showing a benefit of complement inhibition in AMD raises the prospect of more complex mediators at play. Substantial evidence supports the role of para-inflammation in maintaining homeostasis in the retina and choroid. With increasing age, a decline in immune system regulation, known as immunosenescence, has been shown to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 205 publications
0
2
0
Order By: Relevance
“…Inflammaging and immunosenescence have received substantial attention in ocular disease in recent years, including age-related macular degeneration ( 53 ) and uveitis ( 54 ). While evidence on the humoral immune response with age is limited, an increasing cellular-immune dysfunction, a vanning proliferation of antigen-specific lymphocytes, a reduced cytokine production, and a lower activation level of cytotoxic and natural killer cells ( 55 , 56 ) have been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammaging and immunosenescence have received substantial attention in ocular disease in recent years, including age-related macular degeneration ( 53 ) and uveitis ( 54 ). While evidence on the humoral immune response with age is limited, an increasing cellular-immune dysfunction, a vanning proliferation of antigen-specific lymphocytes, a reduced cytokine production, and a lower activation level of cytotoxic and natural killer cells ( 55 , 56 ) have been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Research on aging choroidal endothelial cells in rhesus monkeys reveals high levels of SA-β-Gal and abnormal cytoskeletal activity, sensitizing choriocapillaris to MAC-induced endothelial dysfunction [73]. Increasing evidence suggests that mitochondrial dysfunction plays a critical role in microvascular aging, and the accumulation of DNA damage in the aging vasculature may contribute to replicative senescence [27,[74][75][76].…”
Section: Molecular Insights Into Choroidal Vascular Agingmentioning
confidence: 99%
“…Although the etiology is incompletely understood, evidence suggests a role for inflammation in AMD pathogenesis and progression . Chronic low-level local inflammation is indicated by the presence of inflammatory mediators in drusen and inflammatory cell infiltrates in affected ocular tissues . Polymorphism has been identified in several immune-related genes associated with the risk of AMD .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Chronic low-level local inflammation is indicated by the presence of inflammatory mediators in drusen 8 and inflammatory cell infiltrates in affected ocular tissues. 9 Polymorphism has been identified in several immune-related genes associated with the risk of AMD. 10 A recent transcriptomewide association study reported marked upregulation of genes associated with complement system activation in advanced AMD (ocular and nonocular tissues).…”
mentioning
confidence: 99%